2000
DOI: 10.1143/jjap.39.583
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Modeling of Xe Vacuum Ultraviolet Emission and Radiative Transfer in a Plasma Display Panel Discharge

Abstract: A detailed study of radiative transfer of vacuum ultraviolet emission in a plasma display panel is presented for the first time. Extensive experimental data obtained from a front panel in a test chamber are compared with a theoretical model. The model accounts for radiation trapping and opacity broadening of resonance lines, as well as the major collisional dynamics among ions, neutrals, and electrons in a xenon/neon discharge. The model was also used to predict the panel illumination effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Some part of the above three-body processes may produce Xe 2 (0 u ϩ ) at higher vibrational levels, which lead to the 152 nm band emission. 17 However, from the observed spectra in the VUV region in usual cases, 18 the wavelength-integrated intensity of the 152 nm band is estimated to be less than 10% to 20% of the intensity of the 173 nm band. There included also is the contribution from Xe(1s 4 ) atoms to the 152 nm band emission as described below.…”
Section: Estimation Of Luminous Efficiencymentioning
confidence: 99%
“…Some part of the above three-body processes may produce Xe 2 (0 u ϩ ) at higher vibrational levels, which lead to the 152 nm band emission. 17 However, from the observed spectra in the VUV region in usual cases, 18 the wavelength-integrated intensity of the 152 nm band is estimated to be less than 10% to 20% of the intensity of the 173 nm band. There included also is the contribution from Xe(1s 4 ) atoms to the 152 nm band emission as described below.…”
Section: Estimation Of Luminous Efficiencymentioning
confidence: 99%
“…27 The equations for the decay rates of Xe * ͑1s 5 ͒ atoms and Kr * ͑1s 5 ͒ atoms are written, respectively, as follows: 28,29 In order to derive the three-body reaction rate constants K i ͑i =1,2,3, etc.͒, we follow the relations between them and the gas density.…”
Section: Three-body Reaction Processesmentioning
confidence: 99%
“…Several studies have been conducted on the modeling and simulation of either the discharge characteristics for PDPs [8][9][10][11] or optical characteristics for liquid crystal displays adopting various optical films [12][13][14][15]. However, to the best of our knowledge, the modeling and simulation of the optical characteristics of PDPs, including the BRCR Simple Model of Bright-room Contrast Ratio Measurement System for … -Tae Won Beom et al performance, has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%